Adapting without Retreating: Responses to Shoreline Change on an Inlet-Associated Coastal Beach. Issue 5 (3rd September 2017) - Fallon, Andrew R.; Hoagland, Porter; Jin, Di; Phalen, William; Fitzsimons, G. Gray; Hein, Christopher J.
ABSTRACT: Coastal barrier systems around the world are experiencing higher rates of flooding and shoreline erosion. Property owners on barriers have made significant financial investments in physical protections that shield their nearby properties from these hazards, constituting a type of adaptation to shoreline change. Factors that contribute to adaptation on Plum Island, a developed beach and dune system on the North Shore of Massachusetts, are investigated here. Plum Island experiences patterns of shoreline change that may be representative of many inlet-associated beaches, encompassing an equivocal and dynamically shifting mix of erosion and accretion. In the face of episodic floods and fleeting erosive events, and driven by a combination of strong northeast storms and cycles of erosion and accretion, the value of the average Plum Island residence increases by 34% for properties on the oceanfront where protection comprises a publicly constructed soft structure. Even in the face of state policies that ostensibly discourage physical protection as a means of adaptation, coastal communities face significant political and financial pressures to maintain existing protective structures or to allow contiguous groups of property owners to build new ones through collective action. These factors mitigate against adapting to shoreline change by retreating from the coast, thereby potentially increasing the adverse effects of coastal hazards.